2020
DOI: 10.12691/jfnr-8-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Agraz (<i>Vaccinium meridionale</i> Swartz) Consumption in Overweight and Obese Women with Metabolic Syndrome

Abstract: Obesity implies higher cardiovascular risk (CVR) than overweight. Polyphenol-rich fruits have shown to ameliorate CVR factors (CVRF). It is not clear whether differential effects could be observed between obese and overweight people consuming these fruits. Objective: To evaluate the effects of agraz on CVRF in overweight and obese women with metabolic syndrome (MetS). Methods: Overweight (n=22) and obese (n=18) women (25-60 years) with MetS, were included in this crossover, double-blind and placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous reports show that agraz berries contain a variety of polyphenolic compounds with bioactive characteristics including high antioxidant capacity, antiproliferative and cytotoxic effects against cancerous cells [ 1 ], cardioprotective properties in trials with ischemia-induced rats [ 2 ], anti-inflammatory effects in overweight individuals [ 3 ], and protective effects against colorectal cancer at in vitro and in vivo levels [ [4] , [5] , [6] , [7] ]. In addition, It has been shown that agraz pomace extracts prevent lipid oxidation in Greek yogurt in pork patties during storage [ [8] , [9] ] also have antimicrobial activity against Gram positive and Gram negative bacteria [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports show that agraz berries contain a variety of polyphenolic compounds with bioactive characteristics including high antioxidant capacity, antiproliferative and cytotoxic effects against cancerous cells [ 1 ], cardioprotective properties in trials with ischemia-induced rats [ 2 ], anti-inflammatory effects in overweight individuals [ 3 ], and protective effects against colorectal cancer at in vitro and in vivo levels [ [4] , [5] , [6] , [7] ]. In addition, It has been shown that agraz pomace extracts prevent lipid oxidation in Greek yogurt in pork patties during storage [ [8] , [9] ] also have antimicrobial activity against Gram positive and Gram negative bacteria [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are well known for their bioactive properties. There are reports of cytotoxic activity of V. meridionale S. on leukemic cell lines (González et al., 2017), cardioprotective properties in ischemia‐induced rats (Shen et al., 2018), weight and blood pressure control in humans plasma antioxidant effects (Torres et al., 2018), modulation of anti‐inflammatory markers on lipopolysaccharide‐challenged macrophages (Arango‐Varela et al., 2020), and anti‐inflammatory and antioxidant effects on overweight women (Marín‐Echeverri et al., 2020).…”
Section: Introductionmentioning
confidence: 99%